PERSEPSI PATNER STRATEGIS TERHADAP KUALITAS LAYANAN (STUDI KASUS PADA JASA LAUNDRY ADI PRATAMA PALEMBANG) - M. Nizar Al Rasyid (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2016)
The research is conducted to Evaluate some illustration about the eligibility criteria of a business in SMEs Blessing as a partner of Unit Textile for confection division in the Department of Industry and Trade of South Sumatra, based on the financial aspect. Research methodology is used both of quantitative and qualitative research. This analysis is required at least seen by Net Present Value (NPV), Internal Rate of Return (IRR) and Net Benefit Cost Ratio (Net B / C). Factors Considered are the estimated investment, working capital, operating costs, maintenance and revenue forecasts The Data were Analyzed by reviewing the theory developed by R.A Supriyono (2010), Yacob Ibrahim (2009). There are five criterias in evaluating the eligibility of a business. The calculation method by using Reviews those roomates is Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) and Break Even Point (BEP). According to the result of analysis businesseligibility find that; Payback Period can Returned the capital about three years and six months (3.24 years), Net Present Value Obtained in a positive (+) value roomates is Rp.273.597.150, Internal Rate of Return is on 37% and 38%, Profitability Index is 2.28 and Break Even Point is Rp. 106 550 and 21 units. By the value of the results can be concluded that SMEs Thanks as as a partner of Unit Textile for confection division in the Department of Industry and Trade of South Sumatra is eligible established.